The student-athletes coping strategy and sources of stress - M.S., Omar Fauzee; Don, Yahya; Samad, Norinda; Abdullah, Nagoor Meera; Parnabas, Vincent; Nazaruddin, Mohd Nizam; Soh, Kim Geok (International Journals of Multidisciplinary Research Academy, 2014)
The purpose of this study was to examine the sources of stress and coping strategies among university athletes. Fifteen athletes from a selected university Rugby Sport of Excellence Program in Malaysia aged between18 to 23 years old agreed to participate in this study. Starting from the top level, only 7% of the players have the experience playing at national level, a majority of 60% of them have the experience playing at the state level, 20% at the district level while 13% of the players only play at school level. Qualitative methodology was utilized in this investigation and the interview transcript was analyzed inductively. The results show four sources of stress: feeling nervous before the game, injuries, disruption from the audience and personal problems. Whereas, there are five coping strategies: social support, positive self-talk, mind set, remembering previous success and physical preparation. Recommendations were also suggested in the paper.